Nicotinamide riboside kinases regulate skeletal muscle fiber-type specification and are rate-limiting for metabolic adaptations during regeneration - Sonntag, Tanja; Ancel, Sara; Karaz, Sonia; Cichosz, Paulina; Jacot, Guillaume; Giner, Maria Pilar; Sanchez-Garcia, José Luis; Pannérec, Alice; Moco, Sofia; Sorrentino, Vincenzo; Cantó, Carles; Feige, Jérôme N. (Frontiers in Cell and Developmental Biology, 2022)
Nicotinamide riboside kinases (NRKs) control the conversion of dietary Nicotinamide Riboside (NR) to NAD+, but little is known about their contribution to endogenous NAD+ turnover and muscle plasticity during skeletal muscle growth and remodeling. Using NRK1/2 double KO (NRKdKO) mice, we investigated the influence of NRKs on NAD+ metabolism and muscle homeostasis, and on the response to neurogenic muscle atrophy and regeneration following muscle injury. Muscles from NRKdKO animals have altered nicotinamide (NAM) salvage and a decrease in mitochondrial content. In single myonuclei RNAseq of skeletal muscle, NRK2 mRNA expression is restricted to type IIx muscle fibers, and perturbed NAD+ turnover and mitochondrial metabolism shifts the fiber type composition of NRKdKO muscle to fast glycolytic IIB fibers. NRKdKO does not influence muscle atrophy during denervation but alters muscle repair after myofiber injury. During regeneration, muscle stem cells (MuSCs) from NRKdKO animals hyper-proliferate but fail to differentiate. NRKdKO also alters the recovery of NAD+ during muscle regeneration as well as mitochondrial adaptations and ECM remodeling required for tissue repair. These metabolic perturbations result in a transient delay of muscle regeneration which normalizes during myofiber maturation at late stages of regeneration via over-compensation of anabolic IGF1-Akt signaling. Altogether, we demonstrate that NAD+ synthesis controls mitochondrial metabolism and fiber type composition via NRK1/2 and is rate limiting for myogenic commitment and mitochondrial maturation during skeletal muscle repair.